Retrievable nanocomposite catalyst comprising magnetite nanocubes, mesoporous silica scaffold, and Pd nanocatalysts for efficient Suzuki reactions and reduction of nitroaromatics - Kim, Taehyeong; Jeon, Hyeongjin; Wang, Jinghan; Jung, Sunghoon; Cha, Joo Hwan; Liu, Zhengchun; Jang, Ho Won; Shokouhimehr, Mohammadreza; Kim, Dokyoon (Elsevier BV, 2025)
This study reports a magnetically retrievable nanocomposite catalyst, termed PMRNC-Pd, which consists of single-domain ferrimagnetic magnetite nanocubes, porous silica scaffold, and Pd nanocatalysts. The ferrimagnetic property of the nanocubes allows highly responsive magnetic retrieval so that complete isolation of PMRNC-Pd from reaction mixture is achieved within a few seconds. The amine-functionalized porous silica scaffold of PMRNC-Pd helps localize the ferrimagnetic nanocubes and nucleate Pd nanocatalysts discretely and uniformly without requiring any reducing agent. It also enhances the colloidal stability and dispersibility of PMRNC-Pd, thereby preventing its magnetic aggregation-induced diminishing of catalytic activity. Taken together, high efficiency in the Suzuki cross-coupling transformations and reduction of the nitro groups in nitroaromatics is demonstrated, along with the magnetically assisted sustainable recycling of the catalyst.